Does IFRS drive information asymmetry reduction? Evidence from Asean-6 countries - Yousefi Nejad, Maryam; Azlina Ahmad; Ruzita Abdul Rahim; Fairuz Md Salleh (Penerbit Universiti Kebangsaan Malaysia, 2020)
International Financial Reporting Standard (IFRS) is globally accepted as a high-quality reporting standard. Countries implement IFRS because they believe that more disclosure leads to agency costs reduction and may result in adverse selection costs or information asymmetry reduction. However, studies on the relationship between IFRS and information asymmetry have thus far provided mixed evidence. On the other side, there are limited studies in this area that are focused on ASEAN countries. Therefore, more studies are needed to better understand whether IFRS drives information asymmetry reduction especially in ASEAN countries as developing countries. Therefore, this study contributes to knowledge by examining the association between IFRS and information asymmetry within ASEAN-6 countries, as a setting for developing countries. The results of the OLS (Static Panel estimation technique) indicate that IFRS has a negative and significant relationship with information asymmetry. It reveals that IFRS results in information asymmetry reduction throughout ASEAN-6 countries. Besides using the OLS, this study also applies a Generalized Moment Method (GMM) as an additional test, to measure dynamic relationships and correct the potential endogeneity problem between IFRS and information asymmetry. Besides theoretical and methodological contributions, findings of this study are useful for the adopter and non-adopter countries to understand the consequences of IFRS compliance on information asymmetry. The findings provide important inputs to policymakers of Indonesia and Vietnam who are contemplating adopting IFRS.